Comparing ABA, AAB, and ABC Renewal of Appetitive Pavlovian Conditioned Responding in Alcohol- and Sucrose-Trained Male Rats - Khoo, Shaun Yon-Seng; Sciascia, Joanna Marie; Brown, Alexa; Chaudhri, Nadia (Frontiers in Behavioral Neuroscience, 2020)
Conditioned responding can be renewed by re-exposure to the conditioning context following extinction in a different context (ABA renewal), or by removal from the extinction context (AAB or ABC renewal). ABA renewal is robust in Pavlovian and operant conditioning paradigms. However, fewer studies have investigated AAB and ABC renewal of appetitive conditioning, and those that did predominantly used operant conditioning tasks. Renewal has theoretical relevance for extinction, and for exposure-based treatments for substance use disorders that aim to extinguish reactivity to drug-predictive cues. We therefore investigated ABA, AAB and ABC renewal of Pavlovian conditioned responding to cues that predicted either alcohol or sucrose. Male, Long-Evans rats (Charles River) were exposed to either 15% ethanol (Study 1: ‘alcohol’) or 10% sucrose (Study 2: ‘sucrose’) in their home-cages. Next, they were trained to discriminate between two auditory stimuli (white noise and clicker; 10 s) in conditioning chambers equipped with distinct olfactory, visual and tactile contextual stimuli (context A). One conditioned stimulus (CS+) was paired with fluid delivery (0.2 mL/CS+; 3.2 mL/session; alcohol or sucrose in separate experiments) and the second conditioned stimulus (CS-) was not. In all sessions (conditioning, extinction, test), each CS was presented 16 times/session on a variable-time 67 s schedule and entries into the fluid port were recorded. CS+ port entries were then extinguished by withholding fluid delivery in either context A or in a second, different context (context B). Next, we assessed ABA, AAB and ABC renewal in the absence of fluid delivery. During extinction, CS+ port entries were initially elevated in context A relative to context B. ABA renewal of CS+ port entries occurred in both alcohol and sucrose-trained rats. ABC renewal approached statistical significance when data from both experiments were combined. No AAB renewal was observed and, in fact, alcohol-trained rats showed AAB suppression. These results corroborate the reliability of ABA renewal, and suggest that ABC renewal is a modest effect that may require greater statistical power to detect. From a treatment perspective, the lack of AAB renewal suggests that exposure-based treatments for substance use disorders might benefit from implementation in real-world, drug-use contexts.